The reality of workers exercising of Organizational Citizenship Behavior in the Blue Crescent Hospital – Empirical Study – - Hammade, Abdullah Jumaa; Arid, Mahmoud Ali; Hayek, Abdulhalim Abdulaghany (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the reality of workers exercising organizational citizenship behavior in the Blue Crescent Hospital With its various dimensions (Altruism, Courtesy, Sportsmanship, Civic virtue, Conscientiousness), and to achieve the goals of the study, the descriptive analytical approach was used, and the study community consists of medical and administrative workers in the hospital, and the study was applied to a random sample of (187) employees (male- female), and the questionnaire was used as a main tool for data collection, and the application of appropriate descriptive tests and laboratory inferential tests. The study reached a set of results: The results showed that the level of workers practicing of organizational citizenship behavior in the Blue Crescent Hospital was high, and the dimensions were arranged according to the degree of their exercise: Conscientiousness - Courtesy - Altruism - Civic virtue – Sportsmanship). There are no statistically significant differences at the level of significance (α ≤ 0.05) between the averages of the study sample estimates for the degree of exercise of organizational citizenship behavior in the hospital under study attributed to the gender variable. There are statistically significant differences at the level of significance (α ≤ 0.05) between the averages of the study sample estimates to the degree of the practice of organizational citizenship behavior in the hospital under study attributed to the variable of the field of work. There are statistically significant differences at the level of significance (α ≤ 0.05) between the averages of the study sample estimates for the degree of organizational citizenship behavior in the hospital under study attributed to the variable of years of experience in the hospital. In the light of these results, we recommend the need to maintain this high level of organizational citizenship behavior, by: holding works meeting and preparing publications to highlight the concept of organizational citizenship behavior, clarifying its importance, and explaining the positive effects that accrue to the individual and group, the overall picture of the hospital, and the quality of service towards patients.
Keywords: organizational citizenship behavior; altruism; civility; sportsmanship; civilized behavior; awareness of conscience